The influence of recruitment digitalization and candidate experience on job application interest in Indonesia - Ahmad Iqbal Suryana; Titik Rosnani (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
Digital transformation has driven significant changes in recruitment practices across various industrial sectors, marked by the increased use of e-recruitment systems, Applicant Tracking Systems (ATS), and professional social media. Recruitment digitization is considered capable of increasing efficiency, expanding candidate reach, and improving the quality of the selection process. However, its effectiveness is determined not only by technology, but also by the candidate's experience during the recruitment process. This study aims to analyze the influence of recruitment digitization and candidate experience on job application interest in Indonesia. The study used a quantitative approach with a survey method of 226 respondents who had participated in digital recruitment. Data analysis was conducted using Structural Equation Modeling (SEM) through WarpPLS 8.0. The results showed that recruitment digitization had a positive and significant effect on job application interest (? = 0.525; p less than 0.001), and candidate experience had a significant effect (? = 0.354; p less than 0.001). The R² value of 0.711 indicates that both variables are able to explain 71.1% of the variation in job application interest. These findings underscore the importance of developing effective digital recruitment systems and quality candidate experiences to increase applicant engagement.